Applying design patterns to web services architectures a few well-known patterns can simplify your development efforts. - Peltz, Chris (XML journal :the ultimate enterprise resource.)
From the beginnings of the well-known "Gang of Four" design patterns book to more recent publications on J2EE design patterns, the software industry has always tried to find ways to design frameworks, ideas and concepts that could be used repeatedly. With the introduction of Web services technologies, the need for design patterns remains the same.